Diversity of Orchidaceae family in the montane forest in San Ignacio (Cajamarca, Peru) - Calatayud, Gloria (2005)
The insufficient information on the flora, specifically on the Orchidaceae family and the imminent destruction of the forests in the Eastern slope of the Chinchipe river (San Ignacio, Cajamarca), were the reasons that motivated to make the present investigation. The evaluation was carried out in four localities of the county San Ignacio (Cajamarca), during year 2000. Sampling was random with 27 quadrants an altitudinal range of 100 m and comprising an area of 500 m2 each. Plots were distributed between 800 and 2700 m above sea level. According to the Shannon-Wiener Diversity Index diversity is high in the study area (> grade: Loc. Selva Andina: H’ = 5,93 and